Teacher Digital Literacy and Student Outcomes: A Correlation Study in Secondary Schools - Haruko Takahashi; Sota Yamamoto; Lusiana Rahmadani Putri; Fahrizal Fahrizal (Yayasan Adra Karima Hubbi, 2025)
Background. Digital technologies have become integral to secondary education, increasing demands on teachers to possess strong digital literacy. While technology integration is widely promoted, empirical evidence explaining how teacher digital literacy relates to student outcomes remains limited, particularly at the secondary school level where instructional complexity is higher. Purpose. This study aims to examine the correlation between teacher digital literacy and student outcomes in secondary schools, focusing on academic achievement and learning engagement as key indicators of educational effectiveness. Method. The study employs a quantitative correlational research design supported by descriptive case analysis. Data were collected from secondary school teachers and students using standardized digital literacy questionnaires, student engagement instruments, and academic records. Results. The findings reveal a statistically significant positive correlation between teacher digital literacy and student outcomes. A stronger relationship was found with student learning engagement than with academic achievement. Conclusion. The study concludes that teacher digital literacy plays a crucial role in shaping meaningful learning experiences in secondary education.